"Празька весна" 1968 року в Чехословаччині в українській історіографії - Постоловський, Р.; Слесаренко, А. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
У статті розглядається науковий доробок українських істориків щодо дослідження «Празької весни» 1968 року, а також відображення цих історичних подій у мемуарній літературі (мемуари П. Шелеста). Відзначається, що новий етап вивчення політичної історії Чехословаччини 1968 р., який започаткували після «оксамитової» революції 1989 р. чеські та словацькі історики, справив глибокий вплив на українську історичну науку. Великий науковий інтерес до історії Чехії та Словаччини другої половини XX ст. проявляють сучасні українські славісти академічних і вишівських центрів Києва, Харкова, Львова, Ужгорода, Рівного, Чернівців. Серед досліджень вітчизняних істориків автори виокремлюють монографічні праці І. Короля, І. Вовканича, Р. Пилявця, статті С. Віднянського, С. Мотрук, Р. Постоловського, публікації про відлуння подій 1968 р. в Україні В. Дмитрука. The article deals with the scientific achievements of Ukrainian historians concerning the study of the Prague Spring in 1968, as well as the reflection of these historical events in memoir literature (memoirs of P. Shelest). The theme of the Prague Spring, its political defeat has always been given considerable attention in the Ukrainian historical Slavic studies. The influence on the Ukrainian historical science of a new stage in the study of the political history of Czechoslovakia in 1968, which began after the “velvet” revolution of 1989, was made by Czech and Slovak historians. Significant scientific interest in the history of the Czech Republic and Slovakia in the second half of the XX century show modern Ukrainian slavists of academic and university centers of Kyiv, Kharkiv, Lviv, Uzhgorod, Rivne, Chernivtsi, there were separate works, scientific articles, manuals and collective works. Among the studies of domestic historians, the authors singled out the monographic works of I. Korol, I. Vovkanych, R. Pilyavets, articles by S. Vidnyansky, S. Motruk, R. Postolovsky, publications about the echo of events in 1968 in Ukraine V. Dmytruk. The analysis of the national historiography of the Prague Spring shows that the understanding and interpretation of the events of fifty years ago by Ukrainian historians have undergone evolution. Departing from the Communist Party paradigm of anti-socialist rebellion and justifying the intervention of the states of the Warsaw treaty organization of the Soviet period, domestic scientists consider the phenomenon of the Prague Spring as an attempt of democratic transformation of the socialist system by the Czech and Slovak societies.